A PCR-Free Genome Detection of Mycobacterium Tuberculosis Complex in Clinical Samples using MWCNT/PPy/KHApNps Modified Electrochemical Nano-Biosensor. Issue 7 (1st July 2021) - Salimiyan Rizi, Kobra; Meshkat, Zahra; Chahkandi, Mohammad; Gholami, Mehrdad; Sankian, Mojtaba; Ghazvini, Kiarash; Farsiani, Hadi; Aryan, Ehsan; Rezayi, Majid
Abstract : In the perspective of tuberculosis (TB) disease, a necessary issue is the short interval of the correct diagnosis to planning and starting appropriate antibiotic treatment. So, at the first step for the diagnosis of Mycobacterium tuberculosis ( M. tb ) complex, a fast and reliable technique is necessary. The conventional methods have not the sensitivity, discriminatory power, and enough specificity required for immunocompromised persons. The friendly usage, availability, miniaturization, real-time, and continual monitoring properties of nanobiosensors, an interest attracted to them. The formation of a hybridization reaction in DNA biosensors can provide a possibility for point-of-care infectious detection of M. tb in regions with a high burden of tuberculosis. Here, we have developed a rapid, low-cost, PCR-free with high sensitivity and specificity DNA nanobiosensor for M. tb complex detection, using multi-welled carbon nanotubes, polypyrrole, and potassium-substituted hydroxyapatite (KHAp) nanoparticles. The nanocrystalline powder of KHAp was prepared by a facile alkoxide–based sol-gel method. A selectivity assay using Mycobacterium simiae, Rhodococcus, Nocardia, Corynebacterium, exhibited that the proposed biosensor was specific to M. tb complex. This biosensor showed an appropriate linear relationship (R 2 = 0.9906) between the increase in peak current and logarithmic target concentrations from 100 pM to 100 nM, with LOD and LOQ of 50.3 and 167.5 pM, respectively. Its suitable sensitivity was 335.914 μ A nM −1 cm −2 . The response time of this biosensor was 51.3 s. The proposed biosensor remained about 75% of its initial activity after 29 d. The potential application of the nano-biosensor was determined by spike-in experiments to obtain recoveries between 73% and 103.7%.